REALIZATION OF THE PRINCIPLE OF COMMUNICATIVE TEACHING IN STUDIES OF RUSSIAN AS A FOREIGN LANGUAGE - Fisenko, Olga; Katsyuba, Larisa; Satina, Tatyana (Revista Inclusiones, 2020)
The principle of communicative teaching is becoming relevant in connection with the need to reform the system of Russian education. Modernization of the education environment is aimed at using new principles and approaches in the field of teaching of Russian as a foreign language. The communicative principle of teaching of Russian as a foreign language contributes to the formation of a secondary language personality, being capable of intercultural collaboration not only in learning environment but also in professional activities.